Pathways of internalization of the hCG/LH receptor: immunoelectron microscopic studies in Leydig cells and transfected L-cells (The Rockefeller University Press, 1992)
Monoclonal anti-receptor antibodies were used to study the cellular traffic of the hCG/LH receptor by immunoelectron microscopy. The LHR38 antibody was shown to bind to the extracellular domain of the receptor but not to interfere with hormone binding, adenylate cyclase activation or with the rate of internalization of the receptor. Pig Leydig cells and a permanent L-cell line expressing the LH receptor were used for the study. Incubation with LHR38-gold complexes showed the LH receptors to be randomly distributed over the cell surface including the clathrin coated pits. The LH receptors were internalized via a route including coated pits, coated vesicles and multivesicular bodies to lysosomes. This route is different from that observed for beta-adrenergic, muscarinic, and yeast mating factor receptors and considered previously as possibly general for G-protein-coupled receptors. The use of [125I]LHR38 allowed precise measurement of the rate of internalization, showing the existence of a constitutive pathway which was increased 11- fold by hormone administration. Double labeling experiments suggested that the hormone (hCG-Au15nm) and the receptor (labeled with LHR38- Au5nm) have similar routes of endocytosis, both of them being degraded in lysosomes. Studies of the reappearance of LHR38-Au5nm on the surface of the cells and the use of monensin indicated that only a very small proportion of the receptor molecules were recycled to the cell surface. The distribution and the intracellular pathways of LH receptors are very similar in Leydig cells and transfected L-cells. This opens the possibility of using the latter to study, by in vitro mutagenesis, the molecular mechanisms involved in the cellular traffic of LH receptors.